Rancang Bangun Sistem Informasi Penilaian Kinerja Sopir Taksi Menggunakan Metode Scoring System Pada PT. Merpati Wahana Taksi - Carlos, Yulien; Sutanto, Teguh; Soebijono, Tony (Jurnal JSIKA, 2013)
Abstract: PT. Merpati Wahana Taksi is a company that is under the auspices of the Bosowa Group, is engaged in transportation services (taxis), operating around the city of Surabaya, Sidoarjo and Gresik. The taxi driver is a major support for the movement of human resources activities for the company because they are the majority of the company´s revenue can be obtained. Then to improve the quality of the taxi drivers do a performance assessment so we can know exactly how much performance and the performance achieved by each driver. A taxi driver performance appraisal system that objective needs to be developed in PT. Merpati Wahana Taksi to answer the problems that occurred in the performance appraisal process for this. This final project aims to implement an information system that can help in an employee performance appraisal process. Information systems performance assessment taxi driver who applied using the scoring system method aims to help companies in the process of the taxi driver performance appraisal. Based on extensive research and trials against the taxi driver performance appraisal data, show that the system can help the driver management in conducting employee performance appraisal process quickly and effectively. The system can also be used as a reference driver management in granting promotion / relegation and incentives. Keywords: Performance Appraisal, Performance Appraisal of Taxi Driver, PT Merpati Wahana Taksi.